Enhancing Creativity in 5-6 Year Olds: The Impact of Finger Painting Activities - Nadila Raudatul Aisy; Muzakki Muzakki; Ali Iskandar Zulkarnain; Amirah Amirah (Universitas Islam negeri Mahmud Yunus Batusangkar, 2024)
The development of creativity in early childhood refers to the ability to generate new ideas or create works. This study aims to determine the enhancement of creativity in children aged 5-6 years through finger painting activities. The study uses a classroom action research (CAR) approach. The subjects of the study were 13 children in Umar's class, aged 5-6 years, consisting of 8 boys and 5 girls, along with 1 teacher.The results of the research indicate that the creativity of children aged 5-6 years had not fully developed in terms of their ability to imagine and convey their ideas through drawings. In cycles I and II, the children were still unable to draw something according to their imagination. However, after improvements were made to the steps aimed at fostering creativity through finger painting activities, the children's creativity showed improvement.Through finger painting activities, the children were able to generate ideas for their drawings, choose colors, modify their drawings, create works based on their own ideas, produce unique creations, and further develop their ideas. Nevertheless, their creativity had not yet fully developed to its optimal potential.